Pengaruh Social Media Marketing Instagram Terhadap Repurchase Intention Melalui Experiential Marketing dan Brand Trust: Influence of Instagram Social Media Marketing on Repurchase Intention Through Experiential Marketing and Brand Trust - Muhammad Rizky; Yuliati, Lilik Noor; Hasanah, Nur (School of Business, Bogor Agricultural University (SB-IPB), 2023)
This study aims to analyze the influence of Instagram's social media marketing on repurchase intention through experiential marketing and brand trust in the Naboks Bogor brand. The method of the reseach used quantitative with 200 respondents. The data analysis technique used a descriptive analysis, and Structural equation modeling (SEM) test (Analysis Moment of Structural (AMOS)). The results of the study prove that social media marketing has a positive and significant effect on experiential marketing. Social media marketing has a positive and significant impact on brand trust. Brand trust has a positive and significant effect on repurchase intention. In contrast, experiential marketing has a positive and insignificant effect on repurchase intention and social media marketing has a positive and significant effect on repurchase intention. Keywords: brand trust, experiential marketing, repurchase intention, social media, social media marketing